Pengaruh Budaya Sekolah terhadap Karakter Peserta Didik di Sekolah Dasar - Istiqomah Istiqomah; Sri Enggar Kencana Dewi; Nor Kholidin (FingeR: Journal of Elementary School, 2022)
School culture is as character and personality building followed by school members to distinguish between other schools. Good activities and behaviors affects student characters, especially those behaviors are undergone regularly. The formal education, school, those behaviors will form a school culture. The aim of this research is to know how contribute school culture to student characters, to find out the contribution between school culture and student characters and describe the implementation of school culture by inculcating student characters. The method of the research uses quantitative with a survey approach, data collecting technique using questionnaire. The number of samples used is 27 respondents, whereas data analysis technique is validity test, reliability test, normality test, and using simple linear regression with software of SPSS 19.0 version. The result of the research is that positive effect between school culture and student characters. The school culture increases 1% then it will be also followed by improvement of student character is 0,384% where the better culture as if the better student characters. Student characters are influenced by school culture of 17,4% while 82,6% is influenced by other factors outside of variable of research used. Implementation of character cultivation is analyzed though teaching and learning activity processes, curriculum used, development of learning process and school culture, and learning activity center including routine activities, spontaneous activities, exemplary, and conditioning.